The purposes of the dialectic of the ‘self’ and ‘other’ in Athol Fugard’s Sizwe Bansi is Dead and Boesman and Lena . - Haraj, Sahar Abd Al-Ameer; Hashim, Haidar Laique (Advances in Social Sciences Research Journal, 2016)
Athol Fugard’s political drama is socially relevant since they pertain to the dismantling of apartheid and its replacement with a democratic and unracist system. In his plays, the dialectic of the self and other is always present, and its purposes are varied from one play to the other and from one character to the next. These purposes might be useful to the existence of the colonized people. They might strength the psychological, mental or physical position of the character. To make the oppressed able to force the hostile world that accepts them as others, as marginalized people is a necessary goal in these plays of Fugard. He aims to show the obstacles that lead the black and coloured characters of his plays to be the others and how these characters able to overwhelm these obstacles and get their true self.